Pengaruh Penerapan Otonomi Desa Terhadap Partisipasi Masyarakat Dalam Pembangunan (Suatu Studi Di Distrik Saifi Kabupaten Sorong Selatan) - Ajamsaru, Yonadap; Rorong, Arie Junus; Londa, Very (Sam Ratulangi University, 2016)
Abstract: This research moved from the initial observation that the application by the amah VillageAutonomy Law. No. 6 Year 2015 About the Village is not optimal so that the impact on the low participation ofrural communities, especially in the district of South Sorong Regency Saifi. Thus, this study aimed to analyzethe effect of implementation of village autonomy to public participation in the development of Saifi village inthe district of South Sorong regency. Denagn applying the method of descriptive and quantitative approachesand applying imntrumen questionnaire, distributed to 46 people selamnjutnya government officials Kampungdistributed into five villages. After the data and information collected, then processed and analyzed by usingfrequency tables and analysis product moment correlation analysis and simple linear regression to test thehypothesis.The results of data analysis menunkkan that (1). The implementation of village autonomy is in thecategory